Visual Evoked Potentials in Differential Diagnosis of Multiple Sclerosis and Neurobehcet's Disease - (:unkn) unknown (TOHOKU UNIV MEDICAL PRESS, 2008)
Behcet's disease, a multisystemic vascular inflammatory disorder of unknown origin, is relatively rare and central nervous system involvement is seen in 5% of affected individuals. This form of the disease, called as neurobehcet's disease (NB), can be misdiagnosed as multiple sclerosis (MS), a demyelinating disorder of central nervous system, so their differential diagnosis is important. In this study, to identify the parameters of electrophysiological testing that might be useful in their differential diagnosis, we performed evoked potentials (EPs) and electroneuromyography (ENMG) on patients with MS and NB, and on normal volunteers. A total of 95 persons, 55 MS patients, 20 NB patients and 20 normal volunteers between ages 31 and 55, were studied electrophysiologically. Visual evoked potential (VEP), brainstem auditory evoked potential (BAEP), posterior tibial somatosensory evoked potential (SEP) and nerve conduction and needle electromyography studies were performed on all patients and volunteers. All parameters of EPs were compared among the groups. The results of the BAEP and SEP studies did not show statistically significant difference between NB and MS. However, the VEP study indicated that the amplitude values of cortical VEP potentials (P100) in the NB and MS groups were lower than those of the normal group (p < 0.01), and that the amplitudes in the NB group were lower than for the MS group (p < 0.05). Therefore, P100 amplitude measured from peak to peak seems to be more reliable and thus should be used in the differential diagnosis of MS and NB.
Keywords: Neurobehcet's disease; multiple sclerosis; evoked potentials; visual evoked potentials; electromyography; BEHCETS-DISEASE; INVOLVEMENT; NEUROPATHY